Combined reusing of sorghum husk ash and recycled concrete aggregate for sustainable pervious concrete production (2022)
The huge amounts of natural resources and high level of energy consumption in concrete production necessitate the use of agricultural and demolition wastes as alternative construction materials. The present study explores pervious concrete (PC) that includes sorghum husk ash (SHA) and recycled concrete aggregate (RCA) as alternatives to cement and natural aggregate (NA) in standard PC mixtures. PCs were prepared from mixtures derived from replacement levels 0%, 5%, 10%, 15%, 20% and 25% of cement with SHA and 0%, 20%, 40%, 60%, 80% and 100% of NA with RCA. The density, compressive strength and hydraulic properties (void ratio and hydraulic conductivity) of the samples were determined at 28-day using ACI standards. Sustainability efficiency of incorporating SHA and RCA on PC was also investigated using structural efficiency and carbon dioxide (CO2) emission. Their cost effectiveness was equally examined. Results revealed that densities of PC decreased with increase in SHA and RCA amount. Compressive strength and structural efficiency reduced with increase in SHA except at 5% where they were higher than the control. On the other hand, the incorporation of RCA decreased the compressive strength but improved the PC hydraulic properties. CO2 emission and production cost were found reduced with increase in SHA as well as RCA. The maximum reduction of CO2 emission (38.23%) and production cost (51.29%) were obtained when 25% SHA was combined with 100% RCA. The combined usage of SHA and RCA as raw materials in PC was found to be effective in boosting PC’s hydraulic properties at an appropriate compressive strength. The reduction of CO2 discharge and in production cost attributed to the construction materials demonstrates their impacts on mitigating global warming problems and lowering costs of PC production.